CO2 emission, economic development, fossil fuel consumption and population density in India, Pakistan and Bangladesh: A panel investigation. (20th September 2020) - Uzair Ali, Muhammad; Gong, Zhimin; Ali, Muhammad Ubaid; Asmi, Fahad; Muhammad, Rizwanullah
Abstract: The adverse impacts of climate change have occupied central theme of many policy initiatives. This paper investigated the impact of economic development, fossil fuel consumptions and population density on CO2 in India, Pakistan and Bangladesh using annual data over the period 1971–2014. We have applied panel Autoregressive distributed lags model to estimate the long‐run dynamics and Vector error correction model specified Granger causality test for finding the causality direction. Using three multivariate equations model, the empirical outcome of our study has established key associations that have crucial policy implications. Firstly, the results of auto‐regressive distributed lags (ARDL) confirmed the environmental Kuznets curve hypothesis that the relationship between CO2 and economic development is U‐shaped. Moreover, fossil fuel consumption and population density have a positive impact on CO2 emission in the long run. VECM test evidence suggests that short‐run causalities from economic development to CO2, population density to CO2 and fossil fuel consumption to CO2 exist. Secondly, CO2 has a negative impact on economic development while the impacts of fossil fuel, FDI and total exports on economic development have been significantly positive in the long run. In short run, CO2, fossil fuel consumption and FDI Granger cause economic development. Lastly, CO2 emission negatively influences population density while economic development positively affects population density in long run. Moreover, short‐run causalities from economic development to population density and CO2 to population density exit. For policy drives, efficient and low carbon emission technologies should be used.